Genetic diversity of Newcastle disease viruses circulating in wild and synanthropic birds in Ukraine between 2006 and 2015 - Goraichuk, Iryna V.; Gerilovych, Anton; Bolotin, Vitaliy; Solodiankin, Olexii; Dimitrov, Kiril M.; Rula, Oleksandr; Muzyka, Nataliia; Mezinov, Oleksandr; Stegniy, Borys; Kolesnyk, Olena; Pantin-Jackwood, Mary J.; Miller, Patti J.; et al. (Frontiers in Veterinary Science, 2023)
Newcastle disease virus (NDV) infects a wide range of bird species worldwide and is of importance to the poultry industry. Although certain virus genotypes are clearly associated with wild bird species, the role of those species in the movement of viruses and the migratory routes they follow is still unclear. In this study, we performed a phylogenetic analysis of nineteen NDV sequences that were identified among 21,924 samples collected from wild and synanthropic birds from different regions of Ukraine from 2006 to 2015 and compared them with isolates from other continents. In synanthropic birds, NDV strains of genotype II, VI, VII, and XXI of class II were detected. The fusion gene sequences of these strains were similar to strains detected in birds from different geographical regions of Europe and Asia. However, it is noteworthy to mention the isolation of vaccine viruses from synanthropic birds, suggesting the possibility of their role in viral transmission from vaccinated poultry to wild birds, which may lead to the further spreading of vaccine viruses into other regions during wild bird migration. Moreover, here we present the first publicly available complete NDV F gene from a crow (genus Corvus). Additionally, our phylogenetic results indicated a possible connection of Ukrainian NDV isolates with genotype XXI strains circulating in Kazakhstan. Among strains from wild birds, NDVs of genotype 1 of class I and genotype I of class II were detected. The phylogenetic analysis highlighted the possible exchange of these NDV strains between wild waterfowl from the Azov-Black Sea region of Ukraine and waterfowl from different continents, including Europe, Asia, and Africa.